2023
DOI: 10.1002/cncr.34985
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of ibrutinib maintenance following first‐line high‐dose methotrexate‐based chemotherapy for elderly patients with primary central nervous system lymphoma

Abstract: BackgroundElderly patients account for nearly 70% of all primary central nervous system lymphoma (PCNSL) cases. They cannot tolerate aggressive treatment and have poor prognosis with a median overall survival (OS) of less than 2 years and progression‐free survival (PFS) of 6–16 months. Ibrutinib penetrates the blood–brain barrier and has shown activity in PCNSL.MethodsThis prospective study investigated whether ibrutinib maintenance is feasible, and whether it can benefit elderly PCNSL patients in terms of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…The proposal to use ibrutinib as maintenance therapy following salvage WBRT in the treatment of r/r PCNSL to extend the duration of response to the anti-lymphoma treatment is supported by prior literature studies in which single-agent ibrutinib demonstrated safety and efficacy in the treatment of newly diagnosed PCNSL as maintenance therapy [ 10 ] and in the treatment of some r/r PCNSL cases [ 21 , 22 ]. In one phase II study involving 29 r/r PCNSL and 15 secondary CNS lymphoma cases, treatment using single-agent ibrutinib resulted in an overall response rate of 78%, a median progression-free survival (PFS) of 4 months, and a median OS of 19.5 months [ 22 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The proposal to use ibrutinib as maintenance therapy following salvage WBRT in the treatment of r/r PCNSL to extend the duration of response to the anti-lymphoma treatment is supported by prior literature studies in which single-agent ibrutinib demonstrated safety and efficacy in the treatment of newly diagnosed PCNSL as maintenance therapy [ 10 ] and in the treatment of some r/r PCNSL cases [ 21 , 22 ]. In one phase II study involving 29 r/r PCNSL and 15 secondary CNS lymphoma cases, treatment using single-agent ibrutinib resulted in an overall response rate of 78%, a median progression-free survival (PFS) of 4 months, and a median OS of 19.5 months [ 22 ].…”
Section: Discussionmentioning
confidence: 98%
“…Nonstandard consolidation therapy options for PCNSL include high-dose systemic chemotherapy with autologous stem-cell rescue; traditional chemotherapy such as cytarabine + thiotepa followed by carmustine + thiotepa, thiotepa, busulfan, and cyclophosphamide; high dose cytarabine + etoposide; and high-dose cytarabine [ 7 ] and half-dose whole-brain radiation therapy (WBRT) [ 8 ]. Nonstandard maintenance therapy options for PCNSL include monthly HD-MTX, temozolomide, rituximab, lenalidomide, procarbazine, and ibrutinib [ 7 , 9 , 10 ]. More attention has recently been drawn to maintenance therapy to prolong the duration of remission achieved by induction therapy, particularly in the elderly who cannot tolerate consolidation therapies [ 9 ].…”
Section: Introductionmentioning
confidence: 99%